RESPON GURU TERHADAP PEMBELAJARAN ONLINE DI SDN 02 PAMOTAN LAMONGAN - Ani Zulfah, Machnunah; Roni, Abdul (JoEMS (Journal of Education and Management Studies), 2021)
This research was conducted to determine the response by Islamic Education teachers in implementing online learning. This online learning is carried out in all schools in Indonesia, to prevent the spread of the coronavirus (covid-19). The formulation of the problems in this study are: (a) How the response of Islamic Education teachers at SDN 2 Pamotan to online learning. (b) What are the efforts of SDN 2 Pamotan teachers to increase understanding of online learning. This type of research is a qualitative research with descriptive research. Subjects taken are Islamic education teachers at SDN 2 Pamotan. The data collection technique was done by interviewing the Islamic education teacher at SDN 2 Pamotan. The conclusions obtained in this study are: (a). The media used by SDN 2 Pamotan teachers in teaching online is the Whatsapp application only (b) The response of PAI teachers at SDN 2 Pamotan to online learning The majority of teachers say that online learning is not effective.